SWOT ANALYSIS ON TRANSFORMATION OF STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA MEDAN - Ilhamuddin Nasution; Muhammad Lathief Ilhamy Nasution (State Islamic University of North Sumatra Indonesia, 2018)
This SWOT analysis is carried out to encounter the strengths, weaknesses, opportunities and challenges of UIN of North Sumatra in relation to the transformation of its status changes. As is known, before the transformation, this institution had been dealing with the problem of Religion study programs that were quiet. The addition of the Faculty and the New Public Study Program after the transformation certainly added to the difficulty in resolving the study program problem. Because the problem of lonely interest is closely related to the availability of employment, the most effective way to overcome the problem of lonely interest is by opening an employment opportunities for the alumni. The MoU was conducted with various institutions prioritized to market the alumni. Then internally the academicians of UIN of North Sumatra Medan must have the same spirit of realizing a professional education program and a Combined degree so that every alumni of UIN of North Sumatra Medan has a wider opportunity to obtain employment. The conclusion of this study is that in carrying out the transformation of UIN of North Sumatra Medan is supported by several strengths including assets owned, support from the government, community, trustees and alumni. Meanwhile, weaknesses appear on separate campus locations so that student administration services become ineffective and inefficient. The toughest challenge for the transformation of UIN of North Sumatra Medan is the source of funds, because the budget given by the government every year is very limited while the need for fulfillment of facilities and infrastructure cannot be delayed. As a university located in a strategic area with potential natural resources, UIN of North Sumatra Medan has the opportunity to develop its financial resources from several sectors, such as business, hospitality, plantation, fisheries and tourism.